Manajemen Resiko Redesign Sistem Penjajaran Rekam Medis dengan Metode Failure Mode and Effect Analysis (FMEA) - kori puspita ningsih; Ulfa Tunnisa; Nyndita Erviana (Lembaga Penerbitan Universitas Esa Unggul, 2020)
AbstractThe medical record alignment system at Yogyakarta Condong Catur Hospital uses the Straight Numerical Filing (SNF) storage system. Yogyakarta Condong Catur Hospital uses the SNF system which often causes misfiles. Therefore, it is necessary to redesign the medical record alignment system. In redesign activities, proactive risk management is needed to prevent failures and minimize risks when redesigning the medical record alignment system using the Failure Mode and Effect Analysis (FMEA) method. This study aims to analyze the risk management redesign of medical record alignment from Straight Numerical Filing (SNF) to Terminal Digit Filing (TDF) with the FMEA method. Design research using action research. An instrument to measure the risk management of the medical record alignment system from SNF to TDF by applying the 8 steps of FMEA. After redesigning, the decline in RPN occurred. The highest decrease in RPN in the storage process of failure mode medical record